2014
DOI: 10.1016/j.yqres.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Subglacially precipitated carbonates record geochemical interactions and pollen preservation at the base of the Laurentide Ice Sheet on central Baffin Island, eastern Canadian Arctic

Abstract: The mineralogy and isotopic compositions of subglacially precipitated carbonate crusts (SPCCs) provide information on conditions and processes beneath former glaciers and ice sheets. Here we describe SPCCs formed on gneissic bedrock at the bed of the Laurentide Ice Sheet (LIS) during the last glacial maximum on central Baffin Island. Geochemical data indicate that the Ca in the crusts was likely derived from the subglacial chemical weathering Ca-bearing minerals in the local bedrock. C and Sr isotopic analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 62 publications
(109 reference statements)
5
17
0
Order By: Relevance
“…These corresponding types of cryogenic carbonates have been described in the Vestfold Hills of Antarctica (Aharon, 1988), the Chinese Tien Shan Mountains (Liu et al, 2005), and the Barnes Ice Cap on central Baffin Island, in the eastern Canadian Arctic (Refsnider et al, 2014). For the first and third locations listed here, the respective authors reported carbon and oxygen isotopic signal of SPCCs.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…These corresponding types of cryogenic carbonates have been described in the Vestfold Hills of Antarctica (Aharon, 1988), the Chinese Tien Shan Mountains (Liu et al, 2005), and the Barnes Ice Cap on central Baffin Island, in the eastern Canadian Arctic (Refsnider et al, 2014). For the first and third locations listed here, the respective authors reported carbon and oxygen isotopic signal of SPCCs.…”
Section: Introductionmentioning
confidence: 59%
“…This process has been suggested by Refsnider et al (2014) to explain the low δ 13 C of around −9‰ (VPDB) in the SPCCs from the eastern Canadian Arctic. The carbon isotopic composition measured in organic material of sample STB1, around −24.1 ± 0.2‰ (1σ), is fully consistent with the range of the modern upland Alpine (Urseren Valley, southern central Switzerland) soil organic matter from −27 to −21‰ (Schaub and Alewell, 2009).…”
Section: Carbon and Oxygen Isotopic Signalsmentioning
confidence: 68%
See 2 more Smart Citations
“…However, mixing models of meltwater contributions to the ocean typically assume a constant d 18 O w value for the LIS (À25 or À35‰; Aharon, 2006;Carlson, 2009;Carlson et al, 2007;Hill et al, 2006;Obbink et al, 2010), and do not attempt to incorporate the complex spatial heterogeneity in d 18 O w observed in modern continental ice sheets (Masson-Delmotte et al, 2008;Vinther et al, 2009). Attempts to estimate the oxygen isotope composition of parts of the LIS have used measurements of remnant ice such as the Barnes Ice Cap (Hooke, 1976;Hooke and Clausen, 1982), Pleistocene-age groundwater (Hooke and Clausen, 1982;Remenda et al, 1994) and preserved ice wedges (Kotler and Burn, 2000); as well as indirect proxies from subglacial carbonates (Refsnider et al, 2012(Refsnider et al, , 2014 and proglacial lakes (Birks et al, 2007;Buhay and Betcher, 1998;Last et al, 1994;Moore et al, 2000).…”
Section: Introductionmentioning
confidence: 99%